Mengurangi Kecemasan pada Pasien Diabetes Melalui Konseling Kelompok Kognitif Behavioral - Rani Yusriany; Alfi Purnamasari (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2021)
Diabetes Mellitus (DM) is one of the deadliest diseases in the world. Especially in Indonesia, DM is one of the diseases that are often suffered, ranging from mild to serious chronic. The existence of DM suffered by individuals, can affect their psychological health, one of which is anxiety. The purpose of this study was to reduce the anxiety experienced by DM survivors by using cognitive behavior group counseling techniques. The research subjects consisted of 7 DM survivors who came from the XXX Puskesmas in Yogyakarta. The method used in this study is an experiment with one group of DM survivors who have been given the Hamilton Anxiety Rating Scale (HARS) questionnaire. The data collected was then analyzed using the SPSS program through the Wilcoxson test. The results show that cognitive behavior group counseling is significant for reducing anxiety in DM survivors (p 0.018<0,05).